Mantenimiento del banco de prácticas electroneumáticas de la Universidad Antonio Nariño Sede Cartagena (2023)
The Antonio Nariño University, Cartagena campus, has in its workshops academic physical resources that are indispensable for the theoretical and practical learning of the students of the Faculty of Mechanical, Electronic and Biomedical Engineering, but these assets have vean neglected by the entire institutional community, leading them to deterioration and defective operating condition. Therefore, it is sought to implement as a technological project for the Industrial Electromechanical Maintenance program, the implementation of maintenance for laboratory equipment, specifically the "Electropneumatic Practice Bench", acquired by the UAN as an Electromechanical Engineering project in 2015. For the development of this maintenance, it was required the study of technical guidelines and standardized norms, taking them as guides to complement it. Complying with these guidelines, we proceeded with a diagnosis to the electropneumatic practices equipment, in order to detail its operational status and manage information from it to perform maintenance effectively and concisely. Thanks to the development of the maintenance, it is possible to keep a control for the maintenance.